Explicit formulae for Chern-Simons invariants of the twist-knot orbifolds and edge polynomials of twist knots. (September 2016) - Ham, J.; Lee, J.
Abstract: We calculate the Chern-Simons invariants of twist-knot orbifolds using the Schläfli formula for the generalized Chern-Simons function on the family of twist knot cone-manifold structures. Following the general instruction of Hilden, Lozano, and Montesinos-Amilibia, we here present concrete formulae and calculations. We use the Pythagorean Theorem, which was used by Ham, Mednykh and Petrov, to relate the complex length of the longitude and the complex distance between the two axes fixed by two generators. As an application, we calculate the Chern-Simons invariants of cyclic coverings of the hyperbolic twist-knot orbifolds. We also derive some interesting results. The explicit formulae of the -polynomials of twist knots are obtained from the complex distance polynomials. Hence the edge polynomials corresponding to the edges of the Newton polygons of the -polynomials of twist knots can be obtained. In particular, the number of boundary components of every incompressible surface corresponding to slope turns out to be . Bibliography: 39 titles.